Dynamic Cournot Duopoly Game with Delay. (19th June 2014) - Elsadany, A. A.; Matouk, A. E.
Abstract : The delay Cournot duopoly game is studied. Dynamical behaviors of the game are studied. Equilibrium points and their stability are studied. The results show that the delayed system has the same Nash equilibrium point and the delay can increase the local stability region.